2000
DOI: 10.1073/pnas.200360497
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme mimicry by the antiidiotypic antibody approach

Abstract: The concept of ''internal image'' of antiidiotypic antibodies has provided the basis for eliciting catalytic antibodies. A monoclonal IgM 9A8 that was obtained as an antiidiotype to AE-2 mAb, a known inhibitor of acetylcholinesterase, displayed esterolytic activity. Study of recombinant Fab fragments and separate light and heavy chains of 9A8 confirmed that the antibody variable domain encodes the catalytic function, whereas neither part of the primary sequence of the Fab exhibited homology with the enzyme. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 36 publications
(46 reference statements)
5
71
0
Order By: Relevance
“…The remarkable property of idiotypic mimicry has been exploited to develop anti-idiotypic Abzs; monoclonal Abs were selected by immunizing mice with a monoclonal Ab against the active center of acetylcholinesterase, and a monoclonal anti-idiotypic Ab against carboxypeptidase showed catalytic activity similar to the original antigen [41,42]. Anti-idiotypic DNase Abs were obtained by immunization of rabbits with DNAse I [43].…”
Section: The Origin Of Natural Autoimmune Abzymesmentioning
confidence: 99%
“…The remarkable property of idiotypic mimicry has been exploited to develop anti-idiotypic Abzs; monoclonal Abs were selected by immunizing mice with a monoclonal Ab against the active center of acetylcholinesterase, and a monoclonal anti-idiotypic Ab against carboxypeptidase showed catalytic activity similar to the original antigen [41,42]. Anti-idiotypic DNase Abs were obtained by immunization of rabbits with DNAse I [43].…”
Section: The Origin Of Natural Autoimmune Abzymesmentioning
confidence: 99%
“…At the same time, some antiidiotypic Abs against active centers of many enzymes are also catalytically active [8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Healthy humans do more often not demonstrate catalytic Abs or their activities are extremely low.…”
Section: Introductionmentioning
confidence: 99%
“…Immunization of autoimmune-prone MRL-lpr/lpr mice with DNA-protein complexes also results in significantly higher production of anti-DNA Abs and abzymes with DNase activity comparing with nonautoimmune CBA and BALB/c healthy mice [29][30][31]. At the same time, artificial antiidiotypic abzymes can be induced by immunization of animals with different enzymes [23][24][25][26][27][28]. It was first suggested that natural SLE DNase Abzs may be antiidiotypic abzymes to topoisomerase I [53].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported the presence of typical serine proteases like catalytic triad (Ser-His-Asp) in the catalytic Abs (Kolesnikov et al, 2000;Tramontano et al, 2000). Apart from this, recently, Ramsland et al (2006) has shown the presence of an atypical catalytic site in the Yvo IgM Abs, isolated form Waldenstrom's macroglobulinaemia.…”
Section: Investigation Of the Catalytic Site Histidine By Affinity Lamentioning
confidence: 99%